The Impact of Axillary Lymph Node Dissection on Breast Skin Thickening During and After Radiotherapy for Breast Cancer - Torres, Mylin A. (Int J Radiat Oncol Biol Phys, 2016)
PURPOSE: This prospective study was conducted to determine predictors of epidermal thickening during and after whole breast radiotherapy (XRT) using objective measurements acquired with ultrasound. METHODS AND MATERIALS: Following breast conserving surgery, 70 women received a definitive course of whole breast XRT (50 Gy plus boost). Prior to XRT, at week 6 of XRT, and 6 weeks post XRT, subjects underwent objective ultrasound measurements of epidermal thickness over the lumpectomy cavity and all four quadrants of the treated breast. A skin thickness ratio (STRA) was then generated normalizing for corresponding measurements taken of the untreated breast. RESULTS: Baseline measurements indicated that 87% of patients had skin thickening in the treated versus untreated breast (mean increase of 27%, SD of 0.29) prior to XRT. The STRA increased significantly by week 6 of XRT (mean 25% (SD .46) and continued to increase significantly 6 weeks post XRT (mean 33% (SD .46) above baseline measurements (p<0.001 for both timepoints). In multivariable analysis, breast volume (p=0.003) and surgical evaluation of the axilla with full lymph node dissection (p<0.05) predicted for more severe changes in STRA 6 weeks after XRT compared with baseline. STRA measurements correlated with physician ratings of skin toxicity according to RTOG grading criteria. CONCLUSIONS: This is one of the first studies to objectively document that lymph node surgery impacts XRT-induced skin thickening in breast cancer patients. Surgical evaluation of the axilla with a complete lymph node dissection was associated with the most severe XRT-induced skin changes following XRT completion. These results may inform future studies aimed at minimizing side effects of XRT and surgery, particularly when surgical lymph node assessments may not alter breast cancer management or outcome.